Implementation Of Guarantees Of Legal Protection For Women In The Religious Courts In Indonesia - Abdullah, Muhammad Tsabbit; Syaputra, Akmaluddin; Irwansyah, Irwansyah (UNIVERSITAS PAKUAN, 2024)
This paper attempts to discuss the implementation of legal protection for women in the Religious Courts environment. As part of a vulnerable group, women often face obstacles in gaining access to law and justice. For this reason, the Supreme Court of the Republic of Indonesia took the initiative to take concrete steps by issuing Regulation of the Supreme Court of the Republic of Indonesia Number 3 of 2017 concerning Guidelines for Trying Women's Cases in Conflict with the Law. PERMA Number 3 of 2017 then became a reference for all courts under the Supreme Court, including the Religious Courts, to ensure that women's groups have equal access to law and justice. This type of research is qualitative literary research using a literature approach, namely by viewing and understanding documents or other literature related to guaranteeing legal protection for women, especially those related to policies issued by the Religious Chamber. The results of this research conclude that the implementation of guaranteed legal protection for women in the religious justice environment can be seen from the policies issued by the Directorate General of Religious Courts (DITJEN BADILAG MA) together with the Chair of the Religious Chamber, both in the judicial technical scope and in the non-judicial scope. In the non-judicial scope, the Directorate General of Badilag Supreme Court has issued a policy through a Circular or Decree regarding the optimization of services that can support justice seekers, especially vulnerable groups, in obtaining justice quickly, simply and at low cost. As for the judicial technical scope, the Religious Chamber has routinely scheduled chamber plenary meetings related to the fulfillment of women's rights, the results of which were confirmed through a Circular Letter from the Supreme Court.